m6A-Related lncRNAs Are Potential Biomarkers for the Prognosis of Metastatic Skin Cutaneous Melanoma - Huang, Suyang; Lyu, Shanshan; Gao, Zhe; Zha, Weifeng; Wang, Ping; Shan, Yunyun; He, Jianzhong; Li, Yang (Frontiers in Molecular Biosciences, 2021)
Background: The incidence of SKCM has risen more rapidly than any other solid tumor in the past few decades. The median survival for metastatic melanoma is only six to nine months and the 5-year survival rate of patients with conventional therapy is less than 5%. Our aim was to reveal the potential molecular mechanism in m6A modification of lncRNA and provide candidate prognostic biomarkers for metastatic SKCM. Methods: lncRNAs expression level was obtained by re-annotation in TCGA and CCLE datasets. m6A-related lncRNAs were selected though correlation analysis. Univariate cox regression analysis was used to screen out independent prognostic factors. LASSO Cox regression was performed to construct a m6A-related lncRNA model (m6A-LncM). Kaplan Meier analysis and ROC curve were used to assess the prognostic efficacy of this model and candidate lncRNAs. Enrichment analysis was used to explore the candidate genes’ functions. Results: We obtained 1086 common m6A-related lncRNAs after Pesearon correlation analysis in both two datasets. 130 out of the 1086 lncRNAs are independent prognostic factors. 24 crucial lncRNAs were filtered after LASSO Cox regression analysis. All the m6A-LncM and the 24 lncRNAs were related to overall survival. Stratified survival analysis of m6A-LncM showed that the model remains its prognostic efficacy in recurrence, radiation therapy and other subgroups. Enrichment analysis also found these lncRNAs were immune associated. Conclusion: Here, we obtained 24 crucial lncRNAs that may be potential biomarkers to predict survival of metastatic SKCM and may provide a new insight to improve the prognosis of it.